PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT BANK DINAR INDONESIA - Yuliantari, Kartika (www.bsi.ac.id, 2015)
ABSTRACTSociety in general to know that the bank employee had performance (performance) lessprofessional in completing a task. The employee's performance according to the behavior of somebanking issues still exist throughout Indonesia. Relating to the above description, it is necessary toinvestigate the influence of leadership style on employee performance improvement. In this casewill be examined by taking employees of Dinar Bank Indonesia as the object, namely